Urgensi Peran Generasi Muda dalam Meningkatkan Pendidikan Berkualitas - Putri Tsania Azzahra; Masduki Asbari; Devina Evifa Nugroho (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to find out how important the role of the younger generation is in improving quality education and what educators need to improve the quality of Indonesian education. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from the Youtube channel @klasbersama entitled